Pengaruh Bauran Promosi dan Destinasi Wisata terhadap Keputusan Berkunjung pada Wisata Taman Nasional Baluran - Mokhamad Syaefudin Andrianto; Anis Daifatin Masruroh (IPB University, 2020)
Baluran National Park is one of the Indonesian interesting tour destinations to be visited by local and foreign tourists which is located in Situbondo, East Java. Promotion and condition of tourist destination components are needed to attract visitors. This research aimed to determine the effect of the promotion mix and tourist destination components on the decision to visit Baluran National Park. Primary data was taken by observation, interview with managers and also offline and online surveys. Purposive sampling with criteria minimal come in the last 2 years was used and taken of 100 respondents. The analytical method used descriptive analysis and Structural Equation Modeling (SEM) method with the Partial Least Square (PLS) approach. The results of the study showed that from variable promotion mix (advertising, promotion selling, direct marketing, public relation) and tourist destination components (Attraction, Accessibility, Ancillary, Amenities), only 3 variables; promotion selling, Attraction and Amenities were significant affect on visitors decision to come Baluran National Park.